A Comprehensive Review of Clinical Cardiotoxicity Incidence of FDA-Approved Small-Molecule Kinase Inhibitors - Ying Jin; Zhifei Xu; Hao Yan; Qiaojun He; Xiaochun Yang; Peihua Luo (Frontiers Media S.A., 2020)
Numerous protein kinases encoded in the genome have become attractive targets for the treatment of different types of cancer. As of January 2020, a total of 52 small-molecule kinase inhibitors (SMKIs) have been approved by the FDA. With the numerous clinical trials and a heavy focus on drug safety, SMKI-induced cardiotoxicity, which is a life-threatening risk, has greatly attracted the attention of researchers. In this review, the SMKIs with cardiotoxicity incidence were described exhaustively. The data were collected from 42 clinical trials, 25 FDA-published documents, seven meta-analysis/systematic reviews, three case reports and more than 50 other types of articles. To date, 73% (38 of 52) of SMKIs have reported treatment-related cardiotoxicity. Among the 38 SMKIs with known cardiotoxicity, the rates of incidence of cardiac adverse events were QT prolongation: 47% (18 of 38), hypertension: 40% (15 of 38), left ventricular dysfunction: 34% (13 of 38), arrhythmia: 34% (13 of 38), heart failure: 26% (10 of 38) and ischemia or myocardial infarction: 29% (11 of 38). In the development process of novel SMKIs, more attention should be paid to balancing the treatment efficacy and the risk of cardiotoxicity. In preclinical drug studies, producing an accurate and reliable cardiotoxicity evaluation model is of key importance. To avoid the clinical potential cardiotoxicity risk and discontinuation of a highly effective drug, patients treated with SMKIs should be proactively monitored on the basis of a global standard. Moreover, the underlying mechanisms of SMKI-induced cardiotoxicity need to be further studied to develop new therapies for SMKI-induced cardiotoxicity.